2011
DOI: 10.1063/1.3600638
|View full text |Cite
|
Sign up to set email alerts
|

Defects at nitrogen site in electron-irradiated AlN

Abstract: In high resistance AlN irradiated with 2 MeV electrons, an electron paramagnetic resonance (EPR) spectrum, labeled EI-1, with an electron spin S=1/2 and a clear hyperfine (hf) structure was observed. The hf structure was shown to be due the interaction between the electron spin and the nuclear spins of four (27)A nuclei with the hf splitting varying between similar to 6.0 and similar to 7.2 mT. Comparing the hf data obtained from EPR and ab initio supercell calculations we suggest the EI-1 defect to be the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…These findings indicate that the S = 3/2 state of V N 2− might be of potential interest as a defect qubit, but it might be difficult to realize, as highly n- doped w- AlN is difficult to obtain 47 48 . Interestingly, the V N 0 S = 1/2 state has been recently detected using electron paramagnetic resonance 18 19 . Based on these results, we considered the Fermi level range in the vicinity of the stability region of V N 0 , which might be accessible in experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that the S = 3/2 state of V N 2− might be of potential interest as a defect qubit, but it might be difficult to realize, as highly n- doped w- AlN is difficult to obtain 47 48 . Interestingly, the V N 0 S = 1/2 state has been recently detected using electron paramagnetic resonance 18 19 . Based on these results, we considered the Fermi level range in the vicinity of the stability region of V N 0 , which might be accessible in experiments.…”
Section: Resultsmentioning
confidence: 99%
“…We found that negatively charged nitrogen vacancies exhibit localized spin-triplet states in n- type aluminum nitride under realistic strain conditions. Nitrogen vacancies are naturally incorporated in aluminum nitride during crystal growth and they are known to be the main source of the intrinsic n- type behavior of aluminum nitride 18 19 20 21 , thus making the nitrogen vacancy spins easily amenable to experimental investigations 18 19 . Extra n- type doping control might be achievable by introducing substitutional oxygen impurities (O N ) during crystal growth 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the transformation from the shallow donor to the deeper DX state typically requires to overcome a thermal barrier of some 10 to a few 100 meV, at low sample temperatures the donor can remain for a while in its unstable high symmetry shallow state and lead to “persistent photoconductivity” (PPC) after illumination. The influence of the silicon donor related DX centres on the thermal stability of the shallow donor state with S = ½ was also found in electron paramagnetic resonance . Since for the axial symmetry of AlGaN two possible distortions − parallel to and off the normalctrueˆ‐axis − might occur, two DX states with different relaxation energies are expected.…”
Section: Introductionmentioning
confidence: 84%
“…4 In addition, defects on the nitrogen sublattice (either O N or V N ) have been observed by electron paramagnetic resonance (EPR). 5,6 All these defects are expected to introduce defect states in the band gap of AlN (which is 6.2 eV wide); they may cause sub-band-gap light absorption that can interfere with the operation of optoelectronic devices. Despite these initial assignments, an explanation of the various experimental results based on detailed microscopic mechanisms has yet to emerge.…”
Section: Origins Of Optical Absorption and Emission Lines In Alnmentioning
confidence: 99%